Duodenal injuries in blunt trauma abdomen: a retrospective analysis - Purayil, Sreejayan Meethale; Suthan, Arun (International Surgery Journal, 2019)
Background: Blunt trauma to abdomen very rarely produces isolated duodenal injuries and are to the tune of 3-5%. They are associated with high morbidity and mortality because of the diagnostic delay and missed diagnosis. The aim of this study is to discuss the mode of presentation, investigations and treatment options of isolated duodenal injuries in blunt trauma abdomen. Methods: Retrospective analysis of patients with blunt trauma abdomen who presented to surgical department at government medical college, Kozhikode, Kerala was done. Those who sustained isolated duodenal injuries from January 2010 to 2016 January were included in this study. Complex biliopancreatic, bowel and vascular injuries were excluded. Results: For the single D2 injury, primary closure in 2 layers with 2-0 vicryl and 3-0 braided black silk was done with an omental wrap. The D3 and D4 injuries, limited resection of the unhealthy perforated segment including D3 and D4 were done followed by an end to end duodeno jejunostomy and duodenal exclusion by anterior gastrojejunostomy. Leak test was performed, feeding jejunostomy was done. Conclusions: Isolated duodenal injuries due to blunt trauma abdomen are very rare and should be suspected in patients presenting with upper abdominal pain and vomiting after trauma. CECT abdomen helps to detect it. The time interval between the onset and definitive intervention greatly influences the morbidity and mortality in these injuries.